Fiscal policy dynamics under a consolidation constraint: evidence from a sign-restricted SVAR with orthogonalized business cycle and monetary policy for Australia - Inchauspe, Julian (Applied economics, 2021)
In this study, I employ a SVAR method that filters out the business cycle and monetary policy to produce conservative but realistic estimates of fiscal responses and multipliers for Australia that are unavailable in the literature. The expenditure and tax multipliers reach a maximum of 0.73 and 0.54, respectively, but their comparison alternates depending on the time horizon. Using a linear combination of fiscal shocks, I construct conjectural variations to analyse the data dynamics and inform policymaking on ways of restoring economic activity post-Covid-19. Importantly, it is demonstrated that a policy that simultaneously increases expenditure and taxes can serve as both a fiscal stimulus and a debt reduction instrument in the medium run, with dynamics subject to a transitory reverse overshooting. This finding is particularly relevant for policymakers that are adverse to increasing public debt with discretionary fiscal measures.